Exopolysaccharides From Lactobacillus paracasei Isolated From Kefir as Potential Bioactive Compounds for Microbiota Modulation - Bengoa, Ana Agustina; Dardis, Carolina; Gagliarini, Nina; Garrote, Graciela L.; Abraham, Analía G. (Frontiers in Microbiology, 2020)
Microbiota coexists in true symbiosis with the host playing pivotal roles as a key element for well-being and health. Exopolysaccharides from lactic acid bacteria are an alternative as novel potential prebiotics that increase microbiota diversity. Considering this, the aim of the present work was to evaluate the capacity of the EPS produced by two L. paracasei strains isolated from kefir grains, to be metabolized in vitro by fecal microbiota producing short chain fatty acids. For this purpose, fecal samples from healthy children were inoculated in a basal medium with EPS and incubated in anaerobiosis at 37°C for 24, 48, and 72 h. DGGE profiles and the production of SCFA after fermentation were analyzed. Additionally, three selected samples were sequenced by mass sequencing analysis using Ion Torrent PGM. EPS produced by L. paracasei CIDCA 8339 (EPS8339) and CIDCA 83124 (EPS83124) are metabolized by fecal microbiota producing a significant increase in SCFA. EPS8339 fermentation led to an increment of propionate and butyrate, while fermentation of EPS83124 increased butyrate levels. Both EPS led to a profile of SCFA different from the ones obtained with inulin or glucose fermentation. DGGE profiles of 72 h fermentation demonstrated that both EPS showed a different band profile when compared to the controls; EPS profiles grouped in a cluster that have only 65% similarity with glucose or inulin profiles. Mass sequencing analysis demonstrated that the fermentation of EPS8339 leads to an increase in the proportion of the genera Victivallis, Acidaminococcus and Comamonas and a significant drop in the proportion of enterobacteria. In the same direction, the fermentation of EPS83124 also resulted in a marked reduction of Enterobacteriaceae with a significant increase in the genus Comamonas. It was observed that the changes in fecal microbiota and SCFA profile exerted by both polymers are different probably due to differences in their structural characteristics. It can be concluded that EPS synthesized by both L. paracasei strains, could be potentially used as bioactive compound that modify the microbiota increasing the production of propionic and butyric acid, two metabolites highly associated with beneficial effects both at the gastrointestinal and extra-intestinal level.